2007
DOI: 10.1097/01.aog.0000247643.17067.d9
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Behaviors After Universal Screening of Sexually Transmitted Infections in Healthy Young Women

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Women in the active duty U.S. military are exposed to an environment where a high prevalence of sexual risk behaviors such as binge drinking and multiple sexual partnerships exist (13), which may contribute to risk for sexually transmitted infections (STIs) (46). In addition, a large proportion of active duty women are at a higher risk for STIs due to their demographic characteristics such as being of a younger age, unmarried, and of Black race/ethnicity (7), which are risk factors for STI acquisition in the general population (8).…”
Section: Introductionmentioning
confidence: 99%
“…Women in the active duty U.S. military are exposed to an environment where a high prevalence of sexual risk behaviors such as binge drinking and multiple sexual partnerships exist (13), which may contribute to risk for sexually transmitted infections (STIs) (46). In addition, a large proportion of active duty women are at a higher risk for STIs due to their demographic characteristics such as being of a younger age, unmarried, and of Black race/ethnicity (7), which are risk factors for STI acquisition in the general population (8).…”
Section: Introductionmentioning
confidence: 99%
“…Women in the military tend to report less frequent condom use than both their male colleagues 3 and their civilian women peers. 4, 7 In a study of 1,712 women entering U.S. Marines recruit training, 71% reported using condoms inconsistently. 4 Multiple sexual partnerships are also common, as indicated by findings from a study of male and female army recruits in which almost 60% reported more than 1 sexual partner within the past year.…”
Section: Introductionmentioning
confidence: 99%
“…4, 7 In a study of 1,712 women entering U.S. Marines recruit training, 71% reported using condoms inconsistently. 4 Multiple sexual partnerships are also common, as indicated by findings from a study of male and female army recruits in which almost 60% reported more than 1 sexual partner within the past year. 3 However, risk factors for multiple sexual partners within the military have yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…38 Compared to new recruits who tested negative for an STI upon entry in the military, those who tested positive were more likely to test positive again after returning from vacation during recruit training, and those aged 19-21 years who tested positive were more likely to report having a casual sex partner during vacation. 39 Data on the prevalence of other STIs, including syphilis or herpes simplex, among servicewomen is lacking. Overall, the rates of HIV infection within the military are declining but there is a slower decline among women compared to men.…”
mentioning
confidence: 99%